Dampak Digitalisasi Terhadap Produk UMKM dalam Menghadapi Tantangan Peniruan Dihubungkan dengan Hak Kekayaan Intelektual - Najah, Nurun (Universitas Medan Area, 2024)
The purpose of this study is to understand the challenges and importance of UMKM results in Adapting to the Digital Era. The research methodology used is the normative legal research methodology, namely the application of secondary data in the form of articles or books, to complement primary data on laws originating from regulations, and secondary data on laws originating from articles or books. The results of this study are that digitalization has a positive impact on UMKM business actors, because their products are easy to be famous and known to many people, but it can also be negative when viewed from an IPR perspective. The negative is that products that do not violate IPR, are of good quality, good, and have no protection system will give birth to imitation or counterfeit products elsewhere. Digitalization has a huge impact on UMKM, making it easy for UMKM to run their businesses, but not only positive impacts are obtained, negative impacts such as imitation by other parties cannot be denied, to avoid these problems, MSMEs should register their business brands because protecting a brand is very important because the brand functions as an identification mark that identifies the source of goods and services and the relationship between products and producers.